Computational intelligence in telecommunication networks: a review. (2017) - Paul, Avijit; Mukherjee, Amrita; Das, Apurba; Ghosh, Kuntal
The recent increase in the demand for process optimisation, something which we continually learn from nature, help the telecommunication arena to rapidly evolve into a more scalable, dynamic and robust systematic structure. Due to high intricacy and complex dynamism in every consortium of communication topology, especially in this era of big data and IoT, traditional methods fail to provide network performance and desired throughputs accurately. Computational intelligence now-a-days become indispensable for telecommunication due to the tremendous complexity in multidimensional work space and dynamic environment. Advanced high-tech machines should have their own bio-inspired adaptive intelligence with which they will emerge as energy-efficient and sustainable alternatives for our future generations. In this paper, we try to review different evolving intelligent techniques those are implemented in variegated dimensions of optimisations in telecommunication networks.